The Influence of Visionary Leadership and Academic Culture on Lecturer Performance - Junaidi, Junaidi; Susanto, Ahmad; Hadi, Muhamad Sofian; Agrita, Tri Wera; Hidayat, Husnil (Jurnal Prima Edukasia, 2025)
This study examines the combined influence of visionary leadership and academic culture on the performance of lecturers in the Primary Education Study Program at Muara Bungo Muhammadiyah University (PGSD FKIP UMMUBA). This study employed an ex post facto design and involved 39 lecturers as participants. Data were collected through a questionnaire and analyzed using SPSS. The findings show that visionary leadership positively affects lecturer performance, with a significant t-value of 2.376 (p = 0.023). Similarly, academic culture also positively influences lecturer performance, with a t-value of 4.463 (p = 0.000). Additionally, an ANOVA test revealed that both visionary leadership and academic culture together significantly impact lecturer performance, with an F-value of 58.366 (p = 0.001). These results suggest that strengthening both visionary leadership and academic culture can enhance lecturer performance within the PGSD FKIP UMMUBA study program.